The contribution of dance to the development of motor balance of elementary school 1: An integrative review (Research, Society and Development, 2024)
In childhood, the repertoire of movements is strengthened, therefore, sensory integration through dance is an excellent opportunity for the development of motor skills, and special and body perception, in addition to the child having the opportunity to explore the limits of their body. Therefore, teaching through dance is not just a cultural symbol or a form of expression, but a tool that contributes to basic skills, such as “motor balance”. Starting from this scenario, this study aimed at a qualitative strategy, of a descriptive nature, through a literary review, taking as a starting point the objective of this research - which is to verify, through an integrative analysis, studies that address how dance contributes in the development of motor balance in elementary school students, as well as contextualizing the fundamentals of dance, motor balance and their insertion in Physical Education classes, directly benefiting readers and future teachers in the area of Physical Education. It is worth mentioning that the study seeks to bring reflections to interested parties about the contribution of dance in Physical Education, which is so undervalued, as in schools dance is only expressed as a form of entertainment, at events. With this study, it is possible to understand that dance goes beyond this and can contribute to the educational development of students.